Реалізація замкненої 1-форми на замкнених орієнтованих поверхнях - Будницька, Н.В.; Рибалкіна, Т.В. (Український математичний журнал, 2012)
Исследуются замкнутые 1-формы с изолированными нулями на замкнутых ориентируемых поверхностях. Найдены условия, при которых заданные инварианты будут определять замкнутую 1-форму. We study closed 1-forms with isolated zeros on closed oriented surfaces and establish the conditions under which given invariants generate a closed 1-form.